Catalytic combustion system for use in Malaysia small gas turbine: A feasibility study - M. N. M., Jaafar; A. H., Hussain; Mohamad Shaiful Ashrul, Ishak (Praise Worthy Prize S.r.l., 2011)
Link to publisher's homepage at http://www.praiseworthyprize.com